Protective Effects of Salvia miltiorrhizae on Multiple Organs of Rats with Obstructive Jaundice - Zhang Ling; Zhang Xiping; Qiu Fengmei; Yan Ping; Cheng Qihui (Hindawi Limited, 2009)
Purpose. we aim to explore the protective effects of Salvia miltiorrhizae injection on multiple organs of obstructive jaundice (OJ) rats through observing the impact of this injection on the pathological alterations in these organs and the contents of endotoxin, PLA2, and TNF-α in the blood. Methods. A total of 90 mice were randomly divided into sham-operated group, model-control group, and Salvia miltiorrhizae-treated group (n=30). According to the duration of postoperative administration, each group was further divided into two subgroups, namely, 21 d subgroup (consecutive administration for 21 d, n=15) and 28 d subgroup (consecutive administration for 28 d, n=15). After administration, the pathological alterations in multiple organs were observed and the contents of endotoxin, PLA2, and TNF-α in the blood were determined. Results. Compared to model control group, the number of dead rats in treated group decreased though there was no statistical difference between the two groups. The pathological alterations in the liver, kidney, and spleen in treated group showed varying degrees of mitigation. At all time points, the contents of plasma endotoxin declined significantly. On day 28, plasma PLA2 content in treated group was significantly lower than that in model-control group. Conclusion. Salvia miltiorrhizae injection is able to obviously reduce the contents of inflammatory mediators in the blood of OJ rats and exert some protective effects on multiple organs of these rats.